Creep of service-aged welds - Sun, Wei (1996)
The creep behaviour of welds in service-aged pipes are studied. The aims of the research have been achieved using analytical, numerical and experimental approaches to the relevant subjects. Several features of the work are presented: (i) a systematic parametric study of the creep of two-material test specimens including a stress singularity analysis, (ii) an impression creep testing method using a rectangular indenter, which can be applied to study the creep properties in welds, and (iii) methods used for damage constitutive equation generation involving FE-damage modelling of the rupture tests of cross-weld specimens.